Evaluation the Efficacy of Bacteriophage Against Pseudomonas Aeruginosa Isolated from Wound and Burn Infections - Sarah Ahmed Obaid, Rana Mujahid Al-Shwaikh (Pakistan Journal of Medical & Health Sciences, 2022)
One Hundred clinical samples were collected from different skin infection, including wounds and burns from patients in several hospitals in Baghdad governorate. The phenotypic diagnosis of isolated was performed by culturing on MacConkey agar medium and selective cetrimide agar. After a microscopic and biochemical tests diagnosis, the diagnosis was confirmed using Viteck2 system, 42 bacterial isolates were isolated belonging to P. aeruginosa, with ages ranging from (4 days-75 years). The results of sensitivity test with the Kirby–Bauer Disk diffusion technique found that 19 bacterial isolates only were highly resistant by 76.19% to Cefepime, while the resistance to Ciprofloxacin and Gentamicin was 45.2% for each of them. Moreover, it showed resistance to Aztreonem 33.33%, Ceftazidim and Piperacillin 28.5% each of them, while it also showed high sensitivity and low resistance to Imipenem 26.19%. The results revealed that 3 bacteriophages were isolated with different phenotypic characteristics and had an effective effect on isolates resistant to antibiotics and were studied under different conditions such as the change in temperature and incubation period, as well as the difference in glycerol concentrations.